ANALISIS KUALITAS LAYANAN PEMBAYARAN BIAYA PENDIDIKAN ONLINE (BRIVA) PADA BANK RAKYAT INDONESIA (BRI)TERHADAP KUALITAS LAYANAN. (Studi Kasus: Mahasiswa IIBI Darmajaya Lampung) - Pulungan, Muhammad Sadat (Feb Universitas Dirgantara Marsekal Suryadarma, 2022)
In general, there are three roles of banking, namely funding (collecting public funds), Lending (distribution of financial loans or credit), and other services (such as a place of payment or the need for trade transactions), Kasmir (2003). Besides being an institution that collects funds and distributes funds, banks must also improve their ability to collect funds from the public. Quality has a close relationship with consumers, quality provides an impetus to consumers to establish strong ties with the company. In this study, the data collection technique was carried out by distributing questionnaires and interviews to obtain primary data, and literature study to obtain secondary data. This research was conducted at PT. Bank Rakyat Indonesia (BRI) which is used as a place of payment for IBI Darmajaya students, and especially the cash office of PT. Bank Rakyat Indonesia (BRI) Unit IBI Darmajaya Pringsewu Branch Jl. Z.A. Pagar Alam No 93 Bandar Lapung. The results of this study indicate that the quality of services provided by Bank BRI to IBI Darmajaya students in paying online tuition fees consisting of Reliability, Responsiveness, Assurance, Empathy and Tangible have contribution to IBI Darmajaya Student Satisfaction in online tuition payment services. Of the 5 variables that are used as benchmarks for student satisfaction in online tuition services, the responsiveness variable has a smaller perception than expectations, meaning that in these variables students are not satisfied with the services provided by Bank BRI Bank IBI Darmajaya cash office.Â Keywords: Service Quality